The AI-Powered Revolution: Remote Patient Monitoring Technologies for Chronic Disease Management - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The AI-Powered Revolution: Remote Patient Monitoring Technologies for Chronic Disease Management The global burden of chronic diseases—such as heart fai...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care